2016
DOI: 10.1002/anie.201511007
|View full text |Cite
|
Sign up to set email alerts
|

Organo‐Iodine(III)‐Catalyzed Oxidative Phenol–Arene and Phenol–Phenol Cross‐Coupling Reaction

Abstract: The direct oxidative coupling reaction has been an attractive tool for environmentally benign chemistry.Reported herein is that the hypervalent iodine catalyzed oxidative metalfree cross-coupling reaction of phenols can be achieved using Oxone as at erminal oxidant in 1,1,1,3,3,3-hexafluoropropan-2-ol (HFIP). This method features ah igh efficiency and regioselectivity,a sw ell as functional-group tolerance under very mild reaction conditions without using metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 97 publications
0
41
1
3
Order By: Relevance
“…Carbon–carbon bond formation underpins almost every synthetic undertaking and oxidative processes that unite two nucleophilic partners, at the expense of a C−H bond in each partner, are at the forefront of synthetic technology. Such couplings are typically achieved using stoichiometric metals, or metal catalysts, however, metal‐free processes that do not rely on expensive metal catalysts, and do not generate metallic waste, are desirable …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon–carbon bond formation underpins almost every synthetic undertaking and oxidative processes that unite two nucleophilic partners, at the expense of a C−H bond in each partner, are at the forefront of synthetic technology. Such couplings are typically achieved using stoichiometric metals, or metal catalysts, however, metal‐free processes that do not rely on expensive metal catalysts, and do not generate metallic waste, are desirable …”
Section: Methodsmentioning
confidence: 99%
“…Adding the oxidant and activator in portions greatly improved reaction efficiencya nd product 2a was isolated in 84 %y ield (entry 2). Control experiments revealed that 3a' ', TFA, and TFAA were all essential for the reaction to proceed (entries [3][4][5]. Other terminal oxidants (e.g.…”
mentioning
confidence: 99%
“…Another approach is the direct C−H activation by the means of chemical oxidizers to create the desired arylic C−C bond (Scheme ) . Recently, Kita and co‐workers reported an organo‐iodine(III)‐catalyzed pathway to access the desired cross‐coupling products . Unfortunately, this method is very tedious and needs Oxone™ as a terminal oxidant.…”
Section: Figurementioning
confidence: 99%
“…[10] Recently,K ita and co-workers reported an organo-iodine(III)-catalyzed pathway to access the desired cross-coupling products. [11] Unfortunately,this method is very tedious and needs Oxone as at erminal oxidant. Furthermore,t he reported scope for 4,4'-biphenols in that work was rather limited.…”
mentioning
confidence: 99%
“…[ ][ ] However, this approach required a large excess of the arene and high temperatures, often resulting in regioisomeric mixtures of products and low functional group tolerance. More efficient processes were possible only in special cases, such as coupling with activated azoles or perfluorinated benzene rings. [ ][ ] Therefore, the availability of electrophilic indole or pyrrole synthons able to react with nucleophilic arene partners by C–H functionalization would tremendously enhance the range of accessible arylated heterocycles.…”
Section: Introductionmentioning
confidence: 99%